The willingness to adopt the Internet of Things (IoT) conception in Taiwan’s construction industry - Chen, Jieh-Haur; Ha, Nguyen Thi Thu; Tai, Hsing-Wei; Chang, Chao-An (Journal of Civil Engineering and Management, 2020)
Internet of Things (IoT) conception has become a popular trend among industries. Many have already adopted the technology and put it into practice. IoT can incentive and change the way people conduct business in the construction industry. The objective of the research is to figure out the impact factors that influence practitioners’ willingness to adopt IoT in Taiwan’s construction industry. The hypothesis was developed based on a comprehensive literature review and the concept of the Unified Theory of Acceptance and Use of Technology (UTUAT). The UTUAT framework and hypotheses developed included 5 main hypotheses, 6 aspects and 33 stems. A pilot study aimed at experienced practitioners in the industry was carried out before the full-scale survey to adjust the stems. The adjusted questionnaire including 31 stems belonging to 7 aspects was then distributed to practitioners. A total of 282 valid questionnaires distributed were collected and 6 types of analysis (descriptive statistics, reliability, validity, t-test, one-way of variance, and structural equation modelling). The findings including (1) anticipated benefits significantly affect the users’ willingness to adopt IoT; (2) anticipated efforts significantly affect the users’ willingness to adopt IoT; (3) societal expectations significantly affect the users’ willingness to adopt IoT.